1977
DOI: 10.1002/bbpc.19770811208
|View full text |Cite
|
Sign up to set email alerts
|

The Triplet State of 3‐Nitropyrene

Abstract: Ahstir(ltionss(lakrren, sidirhuv und ulrr~i~iolerr Fwit, Rorfikale 1 PhorochPmk3-nitropyrene was exposed to a 347.2 nm laser flash in dilute solutions of organic solvents and in aqueous micellar solutions. It was found that the triplet state is formed with a quantum yield of 0.6. The triplet absorption spectrum shows a red shift with increasing polarity of the solvent. Triplet-triplet energy transfer experiments with anthracene, pyrene and perylene were performed to obtain both the energy (190 & 10 kJ/mol) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
23
1

Year Published

1987
1987
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 12 publications
7
23
1
Order By: Relevance
“…The triplet decay rate for bromopyrene in methanol after purification was 19 µs compared to a literature value of 20 µs. 10 Before use, coronene and anthracene were recrystallized from ethanol, and the fluorescence decay lifetimes and absorbance spectra matched the literature results.…”
Section: Methodsmentioning
confidence: 93%
“…The triplet decay rate for bromopyrene in methanol after purification was 19 µs compared to a literature value of 20 µs. 10 Before use, coronene and anthracene were recrystallized from ethanol, and the fluorescence decay lifetimes and absorbance spectra matched the literature results.…”
Section: Methodsmentioning
confidence: 93%
“…Similar high triplet yields have been reported for other nitro-PAHs. 11,14,15,27,28 Attention is now shifted to the transient species at 445 nm. As shown in Figures 3i and S3, this transient species persists after the triplet-state signal has decayed, regardless of whether N 2 , O 2 , or ferrocene is added to the solution.…”
Section: The Journal Of Physical Chemistry Lettersmentioning
confidence: 98%
“…Recent time-resolved investigations of mononitropyrenes and nitronaphthalenes have shown that ultrafast intersystem crossing occurs through a doorway triplet state (T n ), which leads to the population of the lowest-energy triplet state (T 1 ) in high yield. A stable aryloxy radical has also been characterized, ,, , which leads to the formation of several major products. , The excited-state mechanism by which this radical intermediary is formed is uncertain and continues to be a topic of debate. , , , ,, …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Significant differences were also observed when their photochemical behavior in the surfaces was compared to that in solution. 10 Studies on the characterization of the participating excited states and reactive intermediate species in the photochemistry of nitropyrenes are mostly limited to the mononitropyrenes. 10−18 The excited-state dynamics and primary photochemical processes of nitronaphthalene 19−27 and nitroanthracene 28 derivatives have also received prominent attention, whereas investigations focusing on the excited-state dynamics of dinitropyrenes have received less scrutiny.…”
Section: Introductionmentioning
confidence: 99%